Forgiveness therapy to increase psychological well-being of family caregivers of patients with schizophrenia - Rismarini, Nadya Anjani; Hasanat, Nida Ul (Faculty of Psychology, Universitas Negeri Yogyakarta, 2022)
Schizophrenia is a severe mental disorders with the highest prevalence among many in Indonesia. Family members who are involved in patients' recovery process may experience subjective burden such as psychological distress and negative emotions, which in turn decrease their psychological well-being. An intervention may be needed to enhace the psychological well-being of family caregivers. This study aimed to investigate the influence of Forgiveness Therapy to psychological well-being in family caregivers of schizophrenic patients. This study used single-case A-B-A design with 3 participants. Caregivers' forgiveness and psychological well-being measured using Heartland Forgiveness Scale for Caregiver, Forgiveness Checklist, Psychological Well-Being Scale, and Psychological Well-Being Checklist. Data analysis through visual inspection revealed that participants' forgiveness and psychological well-being score increased during and after therapy and descriptive analysis showed that participants experienced therapeutic impacts in psychological well-being dimensions. However, this result could not be confirmed as the effect of therapy since the baseline of psychological well-being for these three participants appeared to be unstable. In conclusion, Forgiveness Therapy in this study could not increase the psychological well-being of family caregivers of patients with schizophrenia.